Effect of Financial Resources in Agriculture Production of Nepal - Baidya, Kriti (Journal of Business and Social Sciences Research, 2019)
This study aims to assess the effect of different financial resources such as government expenditure, foreign grant, foreign loan and bank loan in agriculture production of Nepal. For this study six different productions: Wheat, Paddy, Sugarcane, Potatoes, Milk and Egg have been analysed. this study aims to cover the relation of the existing financial resources with the agriculture production using the secondary data from 2003 till 2014 Also related secondary data collected from previous research were analysed to verify the hypothesis and thus structuring the research work. The foreign grant and bank loans have both positive and negative impact on the agriculture production, as in some agriculture production it has significant positive relation whereas in some agriculture production it has negative relation. Out of all the financial resources the foreign loan provided in the agriculture sector has not been able to significantly impact the agriculture sector as none of the production is highly positively significant to the foreign loan. Hence, this study has analysed the different sources of financial resources and its effect on the agriculture production.